1981
DOI: 10.1152/ajpheart.1981.240.4.h620
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting reflex influences of cardiac afferent nerves during coronary occlusion

Abstract: Afferent neurons contained within cardiac sympathetic nerves may have important influences on the circulation when activated during myocardial ischemia. Although such activation is known to reflexly excite upper thoracic sympathetic efferent neurons, effects on other components of sympathetic outflow are unknown. Therefore, cardiac sympathetic afferent nerves were stimulated by occlusion of coronary arteries to investigate their reflex influences on renal sympathetic nerve activity and systemic arterial blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

1981
1981
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 0 publications
0
28
1
Order By: Relevance
“…Occlusion of the left coronary artery also activates receptors innervated by afferent cardiac sympathetic nerves. These cardiac sympathetic afferent nerves can initiate excitatory sympathetic reflexes leading to increased blood pressure (BROWN, 1967;BROWN and MALLIANI, 1971;MALLIANI et al, 1969;UCHIDA and MURAO, 1974;FELDER and THAMES, 1979;WEAVER et a!., 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occlusion of the left coronary artery also activates receptors innervated by afferent cardiac sympathetic nerves. These cardiac sympathetic afferent nerves can initiate excitatory sympathetic reflexes leading to increased blood pressure (BROWN, 1967;BROWN and MALLIANI, 1971;MALLIANI et al, 1969;UCHIDA and MURAO, 1974;FELDER and THAMES, 1979;WEAVER et a!., 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental myocardial infarction, however, COSTANTIN (1963) found that a decrease in sympathetic nerve activity occurred, while MALLIANI and LOMBARDI (1978) and UCHIDA and MURAO (1974) reported an increase in sympathetic nerve activity during coronary occlusion. It has been also reported that myocardial ischemia produced reflexly activated sympathetic nerve activity due to an excitation of cardiac sympathetic afferents and an inhibition mediated by vagal afferents arising from the heart (BROWN and MALLIANI, 1971;FELDER and THAMES, 1979;WEAVER et al, 1981;LOMBARDI et al, 1984). The occurrence of an excitatory cardiocardiac sympathetic reflex response to coronary occlusion, in addition, has been investigated after spinal cord section (MALLIANI et al, 1969;BROWN, 1967;FELDER and THAMES, 1981), which interrupts the supraspinal inhibitory influences on preganglionic sympathetic activity (DEMBOWSKY et al, 1980).…”
mentioning
confidence: 99%
“…[1][2][3] Both experimental and early clinical reports with intracoronary thrombolysis demonstrated a similar sympathoinhibitory reflex response after occlusion and recanalization of the right coronary artery. [4][5][6][7] Although there are only a few clinical studies relative to BJR after intravenous thrombolysis in acute myocardial infarction (MI), this reflex response has earned a reputation as indicator of successful thrombolysis, particularly in the setting of an inferior MI. [7][8][9] However, the pathophysiologic neural mechanisms underlying this phenomenon remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1 Besides Jarisch and Zotterman, 2 who confirmed these results, a host of other investigators contributed greatly to increase our knowledge about the coronary BJR, involving receptors, couched in different terminologies, as ventricular mechanosensitive or chemosensitive neuroreceptors, mostly located in the inferioposterior left ventricular wall, which discharge irregularly and sporadically into small nonmyelinated afferent C-fibers in the vagi. [2][3][4][5] Although these receptors have not been described anatomically or histologically, and the precise mechanisms and the natural stimulus to the cardioinhibitory reflex response are insufficiently understood, stimulation by stretch, distension of an infarcted area, or chemical substances are thought to modulate the arterial baroreflex mediating efferent vagal activation. 17 Fundamental experimental evidence suggests that locally released mediators that occur within minutes after the onset of ischemia, and particularly during reperfusion, such as prostaglandins, serotonin, and oxygenderived free radicals, may activate the cardiac vagal afferent pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation